Monitoring of internal and external loads to interpret acute and chronic fatigue in indoor team sports: A systematic review - Moreno-Villanueva, A.; Rico-González, M.; Pino-Ortega, J. (International Journal of Sports Science & Coaching, 2022)
The aims of this study were: (1) to analyze how the periodization of workloads can induce states of accumulated fatigue in the short, medium and long term in indoor team sports and (2) to identify these periods of fatigue through the interpretation internal and external performance variables. This systematic review was carried out under PRISMA guidelines. The Web of Science, PubMed and Scopus databases were searched for relevant published studies between 1st January 2010 and 25th April 2021. The STROBE scale and MINORS checklist were used to assess the reporting and methodological risk of bias, respectively. Of the 2219 studies initially identified, 20 were selected for a full review. The main conclusions were that a periodic and integrative evaluation of monitoring variables of a different nature is needed to identify states of fatigue accurately and rigorously. The end of the preparatory periods (PPs) and the second phase of the competitive periods (CPs) seem to be the most exhausting moments of the season (high values of RPE, CK, LDH, and oxidative stress markers, and decrease in the T/C ratio). Specifically, congested weeks promote the development of high levels of acute and subacute fatigue (high levels of DOMS and fatigue along with low levels of RPE). Therefore, it is recommended to extend the duration of the preseason and the implementation of more active recovery days during congested weeks, in order to improve resistance to acute and subacute fatigue, and therefore avoid reaching a state of overtraining.